(untitled) (Nigerian Journal of Physiological Sciences, 2024)
The present study evaluates the Peak Expiratory Flow Rate (PEFR) among second-year medical students during a physiology practical session at the College of Medicine and Health Sciences, Baze University, Abuja. Conducted by the Department of Human Physiology’s Laboratory Manual (Exp. 25, Pp. 90), the study involved 20 students (10 males and 10 females) aged 17-25 years. Participants voluntarily engaged in the practical following a 30-minute pre-lab demonstration. Anthropometric measurements, including standing height (in cm) and weight (in kg), were taken, and PEFR was measured in liters/minute using a Mini Wright Peak Flow Meter. Measurements were conducted in triplicate, with the highest value recorded. Descriptive analyses were expressed as mean ± standard deviations (SDs), and data normality was assessed using the Shapiro-Wilk test and boxplot. An unpaired sample t-test was performed to compare anthropometric and physiological variables between genders; with data analysis conducted using IBM SPSS Statistics (Version 27.0). Results indicated that PEFR was significantly higher in males than females (P < 0.001), independent of height, weight, and BMI. Additionally, a significant inverse correlation between PEFR and BMI was observed in males (r = ‒0.67, P < 0.05), whereas no significant correlation was found in females. This study underscores the gender differences in PEFR among medical students and highlights the influence of BMI on PEFR in males. These findings contribute to a better understanding of respiratory physiology in young adults and emphasize the importance of considering gender-specific factors in respiratory assessments